(untitled) (Research, Society and Development, 2021)
Sausage is a meat sausage highly commercialized and consumed by the Brazilian population. However, high handling during processing increases the risk of contamination, requiring quality research to verify that the food is fit for human consumption. Thus, the objective was to evaluate the physical-chemical and microbiological quality of hot dog sausages sold in the city of Mossoró, Rio Grande do Norte, Brazil. The samples were selected and purchased in supermarkets with bulk sales, the temperature being measured at the time of purchase and transported to the laboratory in isothermal boxes for analysis. The temperature, humidity, acidity and pH were investigated, as well as the microbiological quality for total coliforms, thermotolerant coliforms, Salmonella sp, mesophilic bacteria and molds and yeasts. It was found that 70% of the samples had the temperature above the allowed for cold meat sausages. The values ​​found in the analysis of moisture, acidity and pH were satisfactory when compared to current legislation. As for microbiological analyses, it was found that 10% of the sausages evaluated had counts of thermotolerant coliforms above the reference value in the current Normative Instruction and in 20% there was the presence of Salmonella sp, which makes such samples unfit for human consumption, presenting a potential risk public health. The samples showed high counts for aerobic mesophilic bacteria and molds and yeasts, which may suggest possible contamination and unhealthy conditions during processing. Thus, it is necessary to employ good practices in handling, processing and marketing in order to improve the safety and integrity of this product.